Photodynamic Inactivation (Effect of Laser with and Without Photosensitizer) on Viability of Streptococcus Pyogenes - Funjan, Mawada M. (Iraqi Journal of Science, 2022)
This study focused on the bactericidal potency of toluidine blue” TBO”photosensitizer and red laser radiation of 635nmwith different doses against multi-drug resistant streptococcus pyogenes (S. pyogenes) isolated from infected burns wounds to see if it is susceptible to photodynamic inactivation .Atotal of 45 isolates were collected from 38” patients” with infected burnwounds samples were collected from September to December 2019.Burns wounds swabs were employed using standard procedures of swab collection. Among these, eleven isolates were multidrug resistant”S.pyogenes”. More resistant isolates that has been proved to all antibiotics used. This multidrug resistant isolate used in all experiments. Bacterial suspension was diluted by using serial dilutions. The suspension of S.pyogenes in normal saline was treated with” red laser” radiation at a wavelength 635nm with and without “TBO”, and investigated the effect of changing laser doses (3.6 ,7 and 10.8 J/cm2) corresponding to laser exposure time (5,10 and 15 minutes  and different photosensitizer concentrations on viability of “S. pyogenes”isolated from infected burnswounds. The results of this study suggest that multi- drug resistance”S pyogenes” isolated from infected burn wounds inhibited by using photodynamic inactivation mediated by “TBO” and red laser at a wavelength 635 nm.  The effective technique for killing or inhibiting “S. pyogenes isolated from infected burns wounds is the combination of red laser at a wavelength 635nm and TBO. Thecombination of TBO and red laser light prohibit”S. pyogenes”, the optimum results of bacterial inhibition obtained at 50µg/ml, and laser dose 7 J/cm2  corresponding to exposure time 10 minutes.